Crum - Maynard, Lee, 1936- (Book collections on Project MUSE., 2012)
In Crum, a gritty coal town on the West Virginia-Kentucky border, the boys fight, swear, chase and sometimes catch girls. The adults are cramped in and clueless, hemmed in by the mountains. The weight of wonder, dejection, and even possibility loom over this tiny, suffocating town. This story is the tale of Jesse Stone, who doesn't know where he's going, but knows he is leaving, and whose rebellion against the people and the place of his childhood allows him to reject the comfort and familiarity of his home in search of his place in a larger world.